Table of Content - -, (Journal of Humanities & Social Sciences, 2024)
Table of Content:1. Urbanism in the City of Salé: its Patterns and FactorsDr. Nezha Arabi, Dr. Mohamed Aneflouss2. The role of electronic news websites in enhancing national identity among university students  at the University of Jordan  (2011-2015)Mr. Hamza Khalaf Abu Rumman3. Means of calling the Messengers: An analytical study of the calling of the Prophet of God, Abraham, peace be upon himMs. Haila Ali Mohammed Al-Ahmari, Co-Prof. Ahmed Ali Mohammed Al-Zamli4. The Schooling Situation of Special Categories in the Education and Training System, Taza Province – MoroccoMr. Abdelilah El-Alami , Dr. Jaouad El-Bazoui , Dr. Abdelouahed Bouberria5. Netflix Platform Binge Watching and its Relationship to Narrative Transportation Among Saudi YouthMs. Amal Ali Mahnabi, Prof. Shua'a Abdulrahman Aljasir6. Sports violence associated with football matches, a case study of Houari Abu Madian Stadium  in Palestine - Case StudyMr. Salem Kh. Nassr
Keywords: Journal of Human and Social Sciences